Sensitivities of conventional and new electrophysiological techniques in carpal tunnel syndrome and their relationship to body mass index - Aygül, Recep (BioMed Central, 2009)
The purpose of this study is to evaluate prospectively the sensitivities of conventional and new electrophysiological techniques and to investigate their relationship with the body mass index (BMI) in a population of patients suspected of having carpal tunnel syndrome (CTS). In this study, 165 hands of 92 consecutive patients (81 female, 11 male) with clinical diagnosis of CTS were compared to reference population of 60 hands of 30 healthy subjects (26 female and 4 male). Extensive sensory and motor nerve conduction studies (NCSs) were performed in the diagnosis of subtle CTS patients. Also, the patients were divided into subgroups and sensitivities were determined according to BMI. The mean BMI was found to be significantly higher in the CTS than in the control group (p < 0.001). The sensitivity of the median sensory nerve latency (mSDL) and median motor distal latency (mMDL) were 75.8% and 68.5%, respectively. The most sensitive parameters of sensory and motor NCSs were the difference between median and ulnar sensory distal latencies to the fourth digit [(D4M-D4U), (77%)] and the median motor terminal latency index [(mTLI), (70.3%)], while the median-to-ulnar sensory action potential amplitude ratio (27%) and the median-thenar to ulnar-hypothenar motor action potential amplitude ratio (15%) were least sensitive tests. Sensory tests were more sensitive than motor NCSs. Combining mSDL with D4M-D4U, and mMDL with mTLI allowed for the detection of abnormalities in 150 (91%) and 132 (80%) hands, respectively. Measurements of all NCSs parameters were abnormal in obese than in non-obese patients when compared to the BMI. The newer nerve conduction techniques and combining different NCSs tests are more sensitive than single conventional NCS test for the diagnosis of suspected CTS. Meanwhile, CTS is associated with increasing BMI.